An equation for computing expected birth measurements (including birthweight) for the Turkish population (based on pregnancy characteristics) - Özalp, İmran and Ciliv, Gönenç and Erdem, Gülşen and Metcoff, Jack and Costiloe, Paul and Doğramacı, İhsan (The Turkish Journal of Pediatrics, 1981)
Five-hundred twenty-five mothers and their liveborn infants were studied to assess the effects of certain maternal factors and the baby’s sex on birth measurements in the Turkish population. Multiple regression analyses relating the babies’ anthropometric measurements with maternal age, height, pre-pregnancy weight, number of pregnancies and the baby’s sex and gestational age were computed, and the following equation for expected birthweight of an individual baby was obtained: y (expected birthweight) = 13.16 (mother’s age) + 73.81 (gestational age) + 5.65 (pre-pregnancy weight) + 11.31 (mother’s height) + 69.45 (number of pregnancies) — 124.04 (baby’s sex) — 1999.45.